Belief in a Just World and Infantilism as Predictors of Subjective Well-Being - Kryazh, Iryna; Baranov, Vladyslav (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2022)
The article describes the results of a study of belief in a just world, psychological infantilism, and suggestibility as predictors of subjective well-being. The collection of empirical data was carried out in August-September 2022 with citizens of Ukraine. The sample consisted of 71 people (71.8% - women). It was established: Personal beliefs in a just world is a significant predictor of cognitive and emotional components of subjective well-being. The change of residence forced by the martial law increases the emotional discomfort. At the same time, the negative impact of the change of residence on the emotional state of the individual is partially compensated by the strengthening of the personal beliefs in a just world. Psychological infantilism, primarily infantilism of coping behavior, is a negative predictor of subjective well-being. Suggestibility is not a significant predictor of subjective well-being. At the same time, it is directly related to the infantilism of coping-behavior and position of dependency. By supporting these manifestations of infantilism, suggestibility can make a certain contribution to reducing subjective well-being. The article discusses the limitations of empirical research.